Exploring PCAT3 Expression in Arthritis: Proinflammatory Marker Patterns and P53 Involvement - Aida H. Alobaidi; Entkhab M. A. Alanisi; Khalid A. Alyodawi (AUIQ Complementary Biological System, 2024)
This study investigated the role of long non-coding RNA (lncRNA) PCAT3 in arthritis, focusing on its impact on proinflammatory markers. Researchers analyzed both mRNA and protein levels of various proinflammatory markers (TNF-α, IL-1β, IL-4, IL-6, IL-8, IL-10, and IL-13) in arthritis patients and compared them to healthy controls. Additionally, PCAT3 expression was assessed in both patient groups and further investigated using siRNA knockdown in the human synovial cell line SW982. Results revealed distinct expression patterns of proinflammatory markers in arthritis patients, with TNF-α and IL-6 showing the highest levels. PCAT3 expression was significantly elevated in arthritis patients compared to controls. Silencing PCAT3 in SW982 cells led to a significant reduction in the expression of several proinflammatory genes, including TNF-α, IL-1β, IL-6, and IL-10. These findings suggest that PCAT3 plays a role in the pathogenesis of arthritis by contributing to the upregulation of proinflammatory markers. Targeting PCAT3 may offer a potential therapeutic strategy for managing inflammation in arthritis.